Experimental test analysis of hydram pump flow rate using L9 Taguchi at fish pond aquaculture - Joko Yunianto Prihatin; Brillian Adjie Pangestu; Roedy Kristiyono; Sulistyadi Sulistyadi (Journal of Engineering and Applied Technology, 2023)
Good water quality in fish nursery cultivation greatly influences the harvest quality. Temperature and Ph can be maintained properly with proper air circulation. The main problem is that the best flow rate quality in fish ponds of 0.123m3/second is only achieved through the flow from the dam. In this study, the installation of hydram pumps in fish ponds was carried out with the angle of assessing the inflow and discharge to adjust to variations in the diameter of the inlet and outlet pipes, the height of the inlet pipe, and the height of the tank. The experimental design used L9 orthogonal array Taguchi with four replicas. The result of this study was that the maximum value of the input flow rate was 305.73 cm3/second, and the discharge flow rate was 40.35 cm3/second. The maximum value was in the 8th composition; namely, the variation of the inlet pipe height was 200 in, the outlet pipe height was 350 cm, the inlet pipe diameter was 1 in, and the outlet pipe diameter was ½ in.